PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHDAP KINERJA KARYAWAN PADA PT. HADJI KALLA CABANG PALU - NANCY, ASTRIT (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2019)
This study ainst o determine and analyze the effeck of compensation and work discliplineon employee performance of at PT. Hadji Kalla Branch Palu. The population in this studyt were all employees of PT. Hadji Kalla Palu Branch, amounting to 46 employees, the entire population made as respondents (census). This study usesdescriptive descriptive data analysis with a quantitative approach that uses multiple linear regression analysis techniques. The result of this study day that compensation and work discipline have a positive and significant effect on employee performance at PT. Hadji Kalla Palu Branch.